Determination of Hemoglobin Level Among 9-Month-Old Infants Visiting Well Child Clinic - Pongtong Puranitee MD, MHPE; Sajee Fuangfu MD; Oraporn Dumrongwongsiri MD (SAGE Publishing, 2021)
Screening for anemia is recommended among infants aged 9 to 12 months. This study was conducted to determine the prevalence of anemia among 9-month-old infants at Well Child Clinic, and associated factors with anemia. Well Child record of all visits during January to December 2018 were reviewed. Hemoglobin (Hb) was determined by complete blood count (CBC) or point-of-care Hb (POC-Hb). Anemia was found in 99 from 145 infants (68.3%). The prevalence of anemia was 33.3% and 72.8% when tested by CBC and POC-Hb, respectively. Breastfed Infants had significantly lower mean Hb than formula-fed infants. The odd ratio [95% confident interval] of having anemia among infants who were fed with infant formula were 0.37 [0.14-0.94]; P  = .038 when compared to breastfed infants. There was a high proportion of anemia among 9-month-old infants in Rama-WCC and breastfeeding was associated with anemia in infants. The use of POC-Hb may overestimate the prevalence of anemia.